How Do Regulations of Entry and Credit Access Relate to Industry Competition? : International Evidence - Igan, Deniz (IMF Working Papers; Working Paper ;, 2018)
We examine the extent to which regulations of entry and credit access are related to competition using data on 28 manufacturing sectors across 64 countries. A robust finding is that bureaucratic and costly entry regulations tend to hamper competition, as proxied by the price-cost margin, in the industries with a naturally high entry rate. Rigid entry regulations are also associated with a larger average firm size. Conversely, credit information registries are associated with lower price-cost margin and smaller average firm size in industries that rely heavily on external finance-consistent with access to finance exerting a positive effect on competition. These results suggest that incumbent firms are likely to enjoy the rent and market share arising from strict entry regulations, whereas regulations enhancing access to credit limit such benefits.